Characterization of Aldehyde Oxidase (AO) Genes Involved in the Accumulation of Carotenoid Pigments in Wheat Grain - Colasuonno, Pasqualina; Marcotuli, Ilaria; Lozito, Maria L.; Simeone, Rosanna; Blanco, Antonio; Gadaleta, Agata (Frontiers in Plant Science, 2017)
Aldehyde Oxidase (AO) enzyme (EC 1.2.3.1) catalyzes the final steps of carotenoid catabolism and it is a key enzyme in the abscisic acid biosynthesis. AO isoforms are located in the cytosolic compartment of tissues in many plants, where induce the oxidation of aldehydes into carboxylic acid, and in addition, catalyze the hydroxylation of some heterocycles. The goal of the present study was to characterize the AO genes involved in the accumulation of carotenoid pigments in wheat grain, an important quantitative trait controlled by multiple genes. The cDNAs corresponding to the four AO isoforms from Arabidopsis thaliana and five AO isoforms from Brachypodium distachyon were used as query in 454 sequence assemblies data for Triticum aestivum cv. Chinese Spring (https://urgi.versailles.inra.fr/blast/blast.php) to obtain the partial or whole orthologous wheat AO sequences. Three wheat isoforms, designated AO1, AO2 and AO3 were located on the chromosome groups 2, 5 and 7, respectively, and mapped on two consensus wheat maps by SNP markers located within the AO gene sequences. To validate the possible relationships between AO3 genes and carotenoid accumulation in wheat, the expression levels of AO-A3 and AO-B3 gene were determined during the kernel maturation stage of two durum wheat cultivars, Ciccio and Svevo, characterized by a low and high carotenoid content, respectively. Different AO-A3 gene expression values were observed between the two cultivars indicating that the AO-A3 allele present in Ciccio was more active in carotenoid degradation. A gene marker was developed and can be used for marker-assisted selection in wheat breeding programmes.